Eksisi luas karsinoma sel basal pada aksila - Asmaul Khusna; Dinna Devi; Heffi Anindya Putri (Medula, 2026)
Basal cell carcinoma (BCC) is a malignant neoplasm arising from the basal layer of the epidermis and is the most common type of skin cancer, yet it is rarely found in the axillary region due to minimal ultraviolet exposure. Wide local excision is the main therapeutic option to achieve tumor-free margins and prevent recurrence. We report a case of a 46-year-old man presenting with a tumor in the left axilla that had gradually enlarged over one year and developed ulceration within the last three months. The initial lesion appeared as a small pruritic nodule that progressively enlarged and ruptured due to scratching. Physical examination revealed a 5 × 2 × 2 cm tumor with a necrotic base, regular margins, elevated edges, and firm consistency. A clinical diagnosis of BCC was established and confirmed by histopathological examination as nodular type. The patient underwent wide local excision with adequate margins. One-month postoperative evaluation showed good wound healing without signs of recurrence. Repeated trauma and chronic inflammation are considered potential risk factors for BCC in sun-protected areas such as the axilla. BCC rarely metastasizes and has a favorable prognosis when diagnosed and treated early. Adequate wide local excision plays a crucial role in reducing recurrence, with a recurrence rate of approximately 1% when completely excised.